Fungal Involvement in Patients with Paranasal Sinusitis - P Kordbacheh; F Zaini; M Emami; H Borghei; M Khaghanian; M Safara (Tehran University of Medical Sciences, 2004)
Fungal involvement of the paranasal sinuses is frequently observed in the immunocompromised host and it can become lifethreatening if it is not diagnosed. Definitive diagnosis is made by tissue biopsy and culture. In this study biopsy materials of maxillary, ethmoidal and frontal sinuses of 60 patients with clinical manifestation of sinusitis and no response to medical therapy were assessed by mycological and pathological methods for the presence of fungi. Invasive fungal sinusitis was diagnosed in 3 patients and etiologic agents were Candida albicans, Rhizopus sp. and Aspergillus fumigatus. Predisposing factors in these patients were leukemia, diabetes mellitus and previous sinus and polyp surgery, respectively. Allergic fungal sinusitis also was seen in one patient and Alternaria sp. isolated from the biopsy material. Only the patient with allergic form of disease survived but all the patients with invasive form of fungal infection were expired. This clearly underscores the need of early recognition of fungal sinusitis in at risk population in order to start urgent treatment. In this study Nocardia asteroids also was isolated from the biopsy sample in a patient with sinunasal adenocarcinoma.